Radioatividade no ensino médio em uma abordagem Ciência-Tecnologia-Sociedade (CTS) - BRITO, Elisiany dos Santos (2019)
The repercussions of scientific and technological development in everyday life and, consequently, the demand for a critical and active citizen, require the teaching of science a relevant role in basic education. Due to the importance of these issues in the current context, this study presents a didactic proposal for teaching practice in science teaching on the theme radioactivity, built based on the principles of the approach of the Science, Technology and Society movement (STS). The proposal consists in the realization of a scientific event and was applied in two classes of the third year of high school in a state network public school in the urban area of São Luís (Maranhão), aiming to contribute to the formation of a critical, reflective, supportive and responsible citizen, through scientific and technological production issues. Initially, a survey questionnaire was applied on the previous knowledge of the research subjects, in order to guide the approach and the methodology to be used. During the application of the proposal, facts related to the production of the research subjects were recorded, seeking to identify the evolution of knowledge of these subjects on the radioactivity theme and their engagement on scientific and technological issues. The productions, performed with individual and collective presentations, demonstrated in the research subjects the development of attitudes, abilities and values such as self-esteem, creativity, oral communication, collaborative/cooperative learning and solidarity, as well as evidenced developments regarding the awareness of the importance of the issues pertinent to science and technology for the current society. The experience with the didactic proposal offered subsidies for the preparation of a “teaching strategies unit based on the elaboration of events”, with the theme of radioactivity. This material, available in Appendix G, has been proposed to be shared with other teachers, who may use it as educational support in different activities in basic education.